Entrapment of phenol red pH indicator into polyaniline sol-gel / N. Othman, U. M. Noor and Herman, S. H. - Othman, N.; Noor, U. M.; Herman, S. H. (UiTM Press, 2016)
Optical pH sensors offer a promising alternative method over the existence pH electrochemical sensor and other. Due to ability to achieve high performance, electrical passive operation, simplicity and price effectiveness. Recently, significant research efforts have been devoted to pH sensors for the detection of pH variation in high resolution short range changes. It becomes important to consider ways to heighten the sensitivity of the indicator by improving combination of the material and simple method of sensor fabrication. Effort has been put in studying the fabrication and the sensitivity of film towards pH range in physiological application. Most optical sensors consist of an indicator which is immobilized in a polymer matrix. In this research, polyaniline act as a sol - gel matrix to support pH sensitive indicator molecules which is phenol red. Polyaniline has been found to be versatile functional material which is the most suitable organic material to act as a matrix in aqueous medium and capability to sense on pH changes. The sensing capabilities of the device in term its optical absorption intensity with different pH values were explored. Besides that, simpler and low cost methods was prepared and developed. Through the final investigations, it was found that the phenol red immobilized in a polyaniline film on a portion of fiber optic developed by deposited for 4 layers at thickness is 88.46 nm, withdrawal speed with 15 mm/s and re-cladded length is 0.5 cm is the best optimized parameters.